Aminas bioativas durante a maturação de uvas "syrah" produzidas em diferentes regiões e sistemas de condução - Katia de Freitas Fraga (2010)
BIOACTIVE AMINES DURING RIPENING OF SYRAH GRAPES CULTIVATED IN DIFFERENT REGIONS AND TRAINING SYSTEMS. The content of amines is one of the factors determining the quality of grapes and wines. Several factors can affect the levels of amines in grapes and in wine, such as cultivation practices and climatic conditions. Thereis little information on the formation and concentration of amines in grapes in Brazil. To better understand the role of raw material and viticulture processes on the formation of bioactive amines, this study was performed. The levels of amines during ripening of Syrah grapes under different training systems and from different growing regions wereinvestigate. Syrah grapes from vineyards from two regions of Minas Gerais: Pirapora and Três Corações were used. The training systems studied were vertical and Geneva double curtain (GDC). The grapes were crushed manually to obtain the must; the skins and seeds were also separated for analysis. Putrescine, spermidine and spermine were detected in grapes musts, skins and seeds. The levels of these amines varied during ripening. Putrescine and spermidine were detected in every sample. At the time of harvest, the levels of soluble solids, total acidity and pH were influenced by the region and training system employed. The cultivation region affected the levels of amines in grapes at thetime of harvest - the levels of putrescine were higher in musts and skins from Pirapora and seeds from Três Corações. The levels of polyamines were higher in musts from Três Corações and in the skins and seeds from Pirapora. Significant variation of the amines as a function of training system was observed in musts and skins of Syrah grapes on the dayof harvest and in skins at the beginning of ripening. There was significant correlation between the levels of spermidine in grapes from Pirapora and levels of soluble solids and total acidity. Positive correlation was found between the levels of spermidine and putrescine detected in grapes from Três Corações.KEYWORDS: bioactive amines, training systems, Syrah grape.